The Impact of the Social Restrictions Policy on Silent Behavior in South Sulawesi Community Houses - Muh. Mustakim Hasma; Muh. Harun Achmad; Samsu Arif (Fakultas Ilmu Sosial dan Ilmu Pendidikan Universitas Tadulako, 2022)
South Sulawesi was one of the first regions in Indonesia to implement the Large-Scale Social Restriction (LSSR) policy, which runs from April 24 to May 22, 2020, and is one of the non-pharmaceutical strategies used to encourage people to stay at home more in order to suppress the spread of the Covid-19 virus. The purpose of this study is to determine the impact of the LSSR policy on the behavior of people in South Sulawesi who stay silent in their homes, as well as how long the impact will last. The data used is big data in the form of the Google Mobility Report, specifically community mobility data in the form of a percentage change in the number of visits (towards the baseline) for places classified as residential areas measured daily from March 20 to May 22, 2020. The intervention ARIMA model (1,0,0) with the intervention order b=0, r=0, s=8 shows a significant impact from the implementation of LSSR in South Sulawesi using the univariate ARIMA (Autoregressive Integrated Moving Average) statistical analysis method. This is because of contradictory policies that encourage people to begin activities outside the home. The implementation of this policy, which was followed by the beginning of people leaving their homes in May 2020, also had an impact on rising prices due to decreased distribution of goods/services, resulting in scarcity. The study concludes that the LSSR policy has a significant effect on the behavior of people in South Sulawesi staying silent in their homes from its implementation until eight days later.